The Role of Engineering Psychologist in Technical Universities - Ruzmetova Sayyorakhan Timurkhanovna PhD; Gulomjonov Botirjon Gulomjon ogli (European Science Publishing, 2024)
In this article, the engineering psychology to the problem of formation of readiness professional adaptation of technical university students and the main criteria for formation of readiness for professional adaptation are analyzed. Educational activities that ensure the formation of preparation for effective professional adaptation of a technical university student are provided.
Keywords: psychology, engineering, psychologist, professional, education